Cytotoxic Assay of Soursop Leaf Ethanol Extract (Annona muricata Linn.) on Breast Cancer Cell Line (T47D) In Vitro - Ardianti, Dwiana; Suyatmi, .; Mujosemedi, . (Nexus Biomedika, 2015)
Background: Cancer is a genetical disorder which involves dynamic changes of genome, that it causes abnormal cell growth, invasion and metastasis of cell. Breast cancer is found mostly on women. There are many phytochemistry bioactive compounds found in soursop plant. One of the most important component is annonaceous acetogenins. This study aimed to determine the cytotoxic effect of soursop leaf ethanol extract on breast cancer cell line (T47D). Methods: This was experimental laboratory research. The cytotoxic effects of Soursop Leaf Ethanol Extract studied on cell line of breast cancer (T47D) in vitro were measured by MTT assay. The cytotoxic effect of the extract was compared to doxorubicyn. The data were analyzed to determine the inhibitory concentration of 50% (IC50). Results: IC50 of soursop leaf ethanol extract on breast cancer cell line (T47D) was 69.250mg/ml and doxorubicyn was < 0.195mg/ml. Conclusion: Based on the study, soursop leaf ethanol extract has a weak cytotoxic effect on breast cancer cell line (T47D) with IC50 = 69.25 mg/ml. Keywords: MTT assay,Â Soursop Leaf Ethanol Extract, Cytotoxicity, Breast cancer cell line (T47D).